Improving Sugarcane Biomass and Phosphorus Fertilization Through Phosphate-Solubilizing Bacteria: A Photosynthesis-Based Approach - Santos, Hariane Luiz [UNESP]; da Silva, Gustavo Ferreira [UNESP]; Carnietto, Melina Rodrigues Alves [UNESP]; da Silva, Gustavo Ferreira; Fernandes, Caio Nascimento [UNESP]; de Sousa Ferreira, Lusiane [UNESP]; de Almeida Silva, Marcelo [UNESP] (MDPI, 2025)
Phosphorus (P) is essential for sugarcane growth but often presents low agricultural use efficiency. This research evaluated the effects of Bacillus velezensis UFV 3918 (Bv), applied alone or with monoammonium phosphate (MAP), on sugarcane's physiological, biochemical, and biomass variables. Six treatments were tested in a completely randomized design: absolute control (AC), commercial control (CC, full MAP dose), Bv alone, and Bv combined with 1/3, 2/3, or full MAP dose. B. velezensis (Bv) and Bv + 1/3 MAP increased soil P availability by 22%, correlating strongly with physiological, biochemical, and shoot biomass variables. These treatments boosted total chlorophyll content (11.4%), electron transport rate (28.5%), and photochemical quenching (16.9%), resulting in higher photosynthetic efficiency. Compared with CC, net CO2 assimilation, stomatal conductance, and carboxylation efficiency increased by 49.0%, 35.4%, and 72.9%, respectively. Additionally, amino acid content and leaf acid phosphatase activity rose by 12.1% and 13.8%. Key traits associated with biomass production included stomatal density (abaxial face), chlorophyll content, electron transport rate, intercellular CO2 concentration, and leaf acid phosphatase activity. The results highlight the potential of Bv UFV 3918, particularly with reduced MAP doses, to improve sugarcane photosynthesis and biomass accumulation, offering a sustainable and cost-effective fertilization strategy.